The Underlife of a Mathematics Classroom: Latinx Bilinguals Navigating the Official and Unofficial Spaces - Hector Morales, Jr.; Joseph DiNapoli (REDIMAT, 2025)
This paper examines the meaning-making practices of Latinx bilingual students with a challenging mathematics task involving exponential growth. Our aim is to draw a better understanding of how learning takes place among a group of Latinx bilingual students who participate in official and unofficial social spaces in the classroom. Studying the collaborative efforts of Latinx bilinguals, our results suggest these students formed a unique unofficial space, or “underlife”, within the classroom where students dialogically leveraged their communicative resources, practices, and dynamic bilingualism, or counterscript to solve an exponential growth problem. Unfortunately, disruptions to their translanguaging practice in the official space of the classroom did not result in a transformative opportunity for mathematics learning.